NEW VARIETIES OF CAULIFLOWER AND HEADED CABBAGES - E. I. Malakhova; S. K. Temirbekova; I. M. Kulikov; U. V. Afanasyeva (Овощи России)
The new varieties of cauliflower; white and red head cabbages were developed in GNU VSTISP RAAS. The varieties  were included in the State register of breeding achievements  to 01.01.2013. The patents  were received. New varieties have high yield; stable high quality and resistance  to biotic and abiotic stress factors.